2005
DOI: 10.1007/s11745-005-1435-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the transcriptional and fatty acid profiles in response to n−3 fatty acids in SH‐SY5Y neuroblastoma cells

Abstract: Synthesis of docosahexaenoic acid (DHA) from its metabolic precursors contributes to membrane incorporation of this FA within the central nervous system. Although cultured neural cells are able to produce DHA, the membrane DHA contents resulting from metabolic conversion do not match the high values of those resulting from supplementation with preformed DHA. We have examined whether the DHA precursors down-regulate the incorporation of newly formed DHA within human neuroblastoma cells. SH-SY5Y cells were incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 50 publications
3
23
0
3
Order By: Relevance
“…The results on ALA supplementation in growing SH-SY5Y cells support our previous data that ALA is efficiently converted into EPA, DPA and DHA [27]. We had previously shown that the formation of membrane DHA occurs only within a very restricted range of concentration of its upstream precursors (either ALA, EPA or DPA), whereas that of DPA from ALA or EPA follows a saturating doseresponse pattern [27]. Moreover, it has been shown in primary culture that rat astrocytes dosed with ALA incorporate DPA into their membranes, not DHA [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results on ALA supplementation in growing SH-SY5Y cells support our previous data that ALA is efficiently converted into EPA, DPA and DHA [27]. We had previously shown that the formation of membrane DHA occurs only within a very restricted range of concentration of its upstream precursors (either ALA, EPA or DPA), whereas that of DPA from ALA or EPA follows a saturating doseresponse pattern [27]. Moreover, it has been shown in primary culture that rat astrocytes dosed with ALA incorporate DPA into their membranes, not DHA [30].…”
Section: Discussionsupporting
confidence: 89%
“…Neuroblastoma cells in culture are spontaneously depleted in DHA, and they respond to graded concentrations of nonesterified DHA by increasing their membrane DHA to physiological values [28]. These cells also increase their membrane EPA, DPA and DHA in response to supplemental ALA, though the maximum incorporation of ALAderived DHA into phospholipids is 70% lower than that of supplemental DHA dosed at matched concentrations [27]. Since the SH-SY5Y cells can produce membrane EPA, DPA and DHA from supplemental ALA, this model is convenient for studying the regulation of long-chain n-3 synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Estos hallazgos, estimularon el desarrollo de investigaciones sobre el metabolismo del ALA en modelos celulares, animales y humanos, los cuales han entregado información relevante sobre el comportamiento de este ácido graso en diferentes tejidos y condiciones metabólicas Estudios realizados en modelos celulares Los resultados obtenidos a partir de diferentes modelos celulares, han permitido identificar diferencias importantes en el metabolismo de los AGPICL ω-3, dependiendo de la línea celular y la especie de la que provienen las células (33,34). En este sentido, en un estudio realizado en células HepG2 (células cancerígenas hepáticas humanas) en presencia de una elevada concentración de ALA (1,8-72 μM), se produjo un significativo incremento en los niveles de EPA y de ácido docosapentaenoico ω-3 (C22:5 ω-3, DPA), pero no en los de DHA (35).…”
Section: Metabolismo Del Ala Y Conversión Enunclassified
“…Cette voie implique la translocation membranaire, via l'accumulation de la PS, d'un facteur de la voie de signalisation Akt/PI3 kinase, en l'occurrence Akt, qui permet d'inhiber la production de la caspase 3 et par conséquent de limiter le processus de mort neuronale par apoptose (figure 2). [12]. Les données présentées démontrent que l'oestradiol augmente l'incorporation du DHA membranaire issue de la conversion du LNA, ainsi que la transcription génique de la D6 désaturase et de la D-bifunctional protein (DBP) péroxysomale.…”
Section: Effet In Vitro De L'acide Docosahexénoïque (Dha 22 : 6n-3unclassified
“…Les données présentées démontrent que l'oestradiol augmente l'incorporation du DHA membranaire issue de la conversion du LNA, ainsi que la transcription génique de la D6 désaturase et de la D-bifunctional protein (DBP) péroxysomale. Cette dernière enzyme est faiblement exprimée dans ce modèle cellulaire, suggérant que la b-oxydation péroxysomale pourrait constituer l'étape limitante de la synthèse du DHA [12].…”
Section: Effet In Vitro De L'acide Docosahexénoïque (Dha 22 : 6n-3unclassified